New ideas in card and paper crafts - Airey, Graham; Bates, Ben; Price, Ian (New York, Van Nostrand Reinhold, 1973)
Photographs and brief text present progressively more difficult ideas for paper and cardboard creations, from flat modular figures to folded and three-dimensional constructions.
Keywords: Paper work; Paper work